2021
DOI: 10.3233/bd-219006
|View full text |Cite
|
Sign up to set email alerts
|

Profile of anterior gradient 3 (AGR3) mRNA expression and serum levels in benign and malignant breast tumors

Abstract: BACKGROUND: Benign and malignant breast tumors are the most commonly diagnosed tumor in females. Early and accurate diagnosis of malignancy is essential for effective breast cancer treatment. Human anterior gradient 3 (AGR3) has been suggested as a potential biomarker for the early detection and prognostic determination of breast cancer. OBJECTIVE: This study profiles AGR3 mRNA expression and serum protein levels in patients with benign and malignant breast tumors. METHODS: A case-control study was conducted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…However, some studies have revealed contrasting findings. AGR3 mRNA expression was higher in benign than in malignant breast tumors and associated with non-aggressive tumors, which could be used as a marker for less aggressive breast tumors (37). Another study reported that AGR3 was associated with the level of differentiation, slowly proliferating tumors, and more favorable prognosis among breast cancer patients, suggesting its tumor suppressive role (38).…”
Section: Agr3 Expression In Gastric Cancer Tissue Analyzed By (A) Qua...mentioning
confidence: 99%
“…However, some studies have revealed contrasting findings. AGR3 mRNA expression was higher in benign than in malignant breast tumors and associated with non-aggressive tumors, which could be used as a marker for less aggressive breast tumors (37). Another study reported that AGR3 was associated with the level of differentiation, slowly proliferating tumors, and more favorable prognosis among breast cancer patients, suggesting its tumor suppressive role (38).…”
Section: Agr3 Expression In Gastric Cancer Tissue Analyzed By (A) Qua...mentioning
confidence: 99%